Sex Chromosome Turnovers and Stability in Snakes - Pšenička, Tomáš; Augstenová, Barbora; Frynta, Daniel; Kornilios, Panagiotis; Kratochvíl, Lukáš; Rovatsos, Michail (Molecular biology and evolution, 2025)
For a long time, snakes were presented as a textbook example of a group with gradual differentiation of homologous ZZ/ZW sex chromosomes. However, recent advances revealed that the ZZ/ZW sex chromosomes characterize only caenophidian snakes and certain species of boas and pythons have nonhomologous XX/XY sex chromosomes. We used genome coverage analysis in four non-caenophidian species to identify their sex chromosomes, and we examined the homology of sex chromosomes across phylogenetically informative snake lineages. We identified sex chromosomes for the first time in 13 species of non-caenophidian snakes, providing much deeper insights into the evolutionary history of snake sex chromosomes. The evolution of sex chromosomes in snakes is more complex than previously thought. Snakes may have had ancestral XX/XY sex chromosomes, which are still present in a blind snake and some boas, and there were several transitions to derived XX/XY sex chromosomes with different gene content and two or even three transitions to ZZ/ZW sex chromosomes. However, we discuss more alternative scenarios. In any case, we document that (1) some genomic regions were likely repeatedly co-opted as sex chromosomes in phylogenetically distant lineages, even with opposite types of heterogamety; (2) snake lineages differ greatly in the rate of differentiation of sex chromosomes; (3) snakes likely originally possessed sex chromosomes prone to turnovers. The sex chromosomes became evolutionarily highly stable once their differentiation progressed in the megadiverse caenophidian snakes. Snakes thus provide an ideal system for studying the evolutionary factors that drive unequal rates of differentiation, turnovers and stability of sex chromosomes.
Keywords: molekulární evoluce; sex chromosomes; sex determination; reptiles; DNA-seq; Phylogeny; Sex Chromosomes; pohlavní chromozomy; Evolution, Molecular; genomics; qPCR; Female; Biological Evolution; zvířata; ženské pohlaví; Male; fylogeneze; biologická evoluce; hadi; Animals; mužské pohlaví; Snakes